SNOW ALBEDO MODIFICATION: A REVIEW OF LITERATURE. - Slaughter,Charles W. (1969)
A summary of published information on snow albedo modification is presented. Consideration of energy balance parameters is followed by discussion of qualitative and quantitative results of albedo modification, both increasing (lightening) and decreasing (darkening). Practical applications of albedo modification are discussed. (Author)